Molecular markers in bean (Phaseolus vulgaris L.) breeding. - Kelly, James (2016)
Plant breeding methods used to pyramid disease resistance genes generally involve crossing, backcrossing and test crosses in order to verify the presence of desirablecombinations of these genes in the resulting progeny. The epistatic interaction between resistance genes combined with limitations of sample size and the work involved in test crossing results in progeny that do not always possess the desirablecombination of genes. The entire procedure could be made more efficient through the use of molecular markers tightly linked to the resistance genes. Selection for the markers in the absence of the pathogen would result in the indirect selection of resistance genes. The expression of the marker is not masked by any epistatic interaction which commonly occurs with resistance genes. Our bean breeding/genetics group at Michigan State University have successfully tagged the Up-2, Ur-3 genes and the gene block B-190 which confer resistance to bean rust. This achievement has been possible through the use of molecular markers known as RAPD' s (Random Amplified Polymorphic DNA) and populations developed through backcrossing. These molecular markers offcr us the opportunity to pyramid rust rcsistance gene s into specific genotypes in the most efficient way. This breeding strategy will ensure the stability of the same resistance genes.